2004
DOI: 10.1021/nl049341r
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Fabrication of Carbon Nanotube Probe Tips for Atomic Force Microscopy Critical Dimension Imaging Applications

Abstract: We report an innovative approach that combines nanopatterning and nanomaterials synthesis with traditional silicon micromachining technologies for large-scale fabrication of carbon nanotube (CNT) probe tips for atomic force microscopy imaging applications. Our batch fabrication process has produced 244 CNT probe tips per 4-in. wafer with control over the CNT location, diameter, length, orientation, and crystalline morphology. CNT probe tips with diameters ranging between 40 and 80 nm and lengths between 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 26 publications
1
79
0
Order By: Relevance
“…To obtain better lateral resolution, carbon nanotubes are considered the preferred material for use as the probe tip of scanning probe microscopes on the basis of their large aspect ratio and good mechanical properties [43,44]. Even though SWCNTs are expected to provide good images including improved lateral resolution due to their small diameter (close to 1 nm), MWCNTs have provided better lateral images due to their good modulus [45,46]. It was reported that DWCNTs, having a similar diameter to that of SWCNTs and a comparable structural stability to that of MWCNTs, have been successfully attached to an AFM tip and then tested as a promising probe tip [47].…”
Section: Atomic Force Microscopy Tipsmentioning
confidence: 99%
“…To obtain better lateral resolution, carbon nanotubes are considered the preferred material for use as the probe tip of scanning probe microscopes on the basis of their large aspect ratio and good mechanical properties [43,44]. Even though SWCNTs are expected to provide good images including improved lateral resolution due to their small diameter (close to 1 nm), MWCNTs have provided better lateral images due to their good modulus [45,46]. It was reported that DWCNTs, having a similar diameter to that of SWCNTs and a comparable structural stability to that of MWCNTs, have been successfully attached to an AFM tip and then tested as a promising probe tip [47].…”
Section: Atomic Force Microscopy Tipsmentioning
confidence: 99%
“…16,17 These approaches, however, require somewhat complicated, multiple patterning steps. The catalyst dots in both approaches are patterned by the lift-off of the spin-coated polymethyl methacrylate ͑PMMA͒ layer following typical electron-͑e-͒ beam lithography.…”
mentioning
confidence: 99%
“…A reliable and uniform spin coating of a resist layer generally requires a relatively large area, and is difficult to achieve for a tipless cantilever, which has a narrow and elongated geometry. In one of these reports, 16 patterned catalyst dots were formed before the fabrication of the cantilevers, but the catalyst had to be protected by the PECVD-deposited Si 3 N 4 layer in order for the catalyst dots to survive and keep catalytic activity throughout the subsequent microfabrication steps. In the other report, 17 the e-beam lithography steps had to be used twice to pattern a catalyst dot on the commercial tipless cantilever in order to remove the extra Ni catalyst on the cantilever.…”
mentioning
confidence: 99%
“…While there has been impressive progress in MEMS and NEMS resonators, these resonators are mostly chip-based and in-plane and are fabricated using silicon micro and nano-fabrication processes. The development of nanometer scale out-of-plane high aspect ratio resonators have been slow; an example includes the carbon nanotubes reported in the past for scanning probe microscopy (SPM) applications [6,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%